TOTAL SERUM PROTEIN AND CHOLESTEROL CONCENTRATIONS AT INDUCED AND NATURAL PUBERTAL OESTRUS IN INDIGENOUS HEIFERS - R. K. BISWAS2, B. K. SARMAH1 (Indian Journal of Animal Production and Management, 2017)
Twenty prepubertal indigenous heifers (Bos indicus) of Assam aged 18-24 months, weighing 67-90 kg were selected for hormonal induction of oestrus and to compare the serum levels of protein and cholesterol at induced and at natural pubertal oestrus. Another 15 prepubertal indigenous heifers of similar age and body weight served as untreated control. Heifers were examined rectally to ensure that they had no corpus luteum and/or onset of oestrus before treatment. Each of the heifers was treated with Crestar injection containing 3 mg norgestomet and 5 mg oestradiol valerate. Implant was removed on day 9 of insertion and PMSG was administered @ 300 IU. Of 20 treated heifers induced to oestrus, 16 (80%) ovulated, 4 (20%) heifers did not ovulate. Heifers under control group exhibited natural pubertal oestrus at an average age of 33.60 ± 2.81 months. Of these 10 (66.67%) heifers ovulated while 5(33.33%) did not ovulate. Total serum protein concentration in prepubertal heifers before treatment ranged between 7.20 ± 0.10 and 7.65 ± 0.18 g%. The pre-treatment level of total serum protein was lower in prepubertal heifers that did not ovulate subsequently which was significant (P<0.01) in control heifers. The mean total serum protein concentration at oestrus was 7.40 ± 0.10 and 7.67 ± 0.26 g% in ovulated and nonovulated heifers respectively following treatment. The mean serum cholesterol concentration in heifers before treatment ranged between 106.43 ± 7.68 and 155.64 ± 8.04 mg%. In treated heifers the mean serum cholesterol concentration decreased at induced oestrus from that of before treatment levels which was significant (P<0.01) in ovulated heifers. Contrary to the treated group, in control heifers serum cholesterol concentration increased significantly (P<0.01) at pubertal oestrus irrespective of their ovulation status. From the present study it may be concluded that hormonal induction of oestrus in prepubertal heifers was associated with changes in the levels of serum protein and cholesterol. While serum protein concentration could maintain homoeostasis despite hormonal treatment, the level of cholesterol was significantly altered concomitant with bringing about ovulatory oestrus.